Tracing Hybridity in the Provision of ICT-Enabled Agricultural Weather Information Services in Ghana. Issue 1 (3rd April 2021) - Sarku, Rebecca; van Slobbe, Erik; Termeer, Katrien; Chudaska, Rebecca; Siwale, Agatha; Dewulf, Art
Abstract: This study investigates the hybrid informational governance arrangements involved in the provision of ICT-enabled Weather Information Services (WIS) for farming in Ghana. Farmers and organizations providing WIS were interviewed. Findings show that multiple technologies are used by combinations of government, business, and civil society organizations to provide various WIS for farming. The ICT has facilitated the creation of different hybrid informational governance arrangements, categorized as multiplicity, intertwinement, and coalescence, which permits flows of WIS across scales, from international non-state organizations to farming communities, often by-passing national and district-level government organizations. Government organizations remain key players in the provision of WIS.